Inscrutably, actually: hospitality, parasitism, and the silent work of Yoko Ono and Laurel Nakadate†. Issue 3 (2nd September 2018) - Huang, Vivian L.
Abstract : With interest in queer socialities, the author considers Jacques Derrida's provocation in Of Hospitality to "say yes" as hospitable gesture in order to challenge the gendered and racialized demands of this charge. If Orientalist conflations of the East with femininity have in turn sexualized Asian women as simultaneously hypersexual and submissive, then how can we as viewers and readers performatively read Asian femininity in a different, and not anti-relational, orientation to hospitality? Building upon Anna Watkins Fisher's concept of parasitic performance, this article posits inscrutability as a feminist methodology by considering Yoko Ono's performances of Cut Piece and Laurel Nakadate's video Happy Birthday for their interesting solicitations to audience-participants, costars, and viewers.